Breast cancer incidence in the regions of Belarus and Ukraine most contaminated by the Chernobyl accident: 1978 to 2016. Issue 8 (29th October 2020) - Zupunski, Ljubica; Yaumenenka, Alesia; Ryzhov, Anton; Veyalkin, Ilya; Drozdovitch, Vladimir; Masiuk, Sergii; Ivanova, Olha; Kesminiene, Ausrele; Pukkala, Eero; Moiseev, Pavel; Prysyazhnyuk, Anatoly; Schüz, Joachim; et al.
Abstract: Even 30 years after the accident, an association between breast cancer incidence and ionizing radiation exposure from Chernobyl fallout remains uncertain. We studied breast cancer incidence in the most contaminated regions of Belarus (Gomel and Mogilev) and Ukraine (Kyiv, Zhytomyr and Chernihiv) before (1978‐1986) and after (1987‐2016) the accident. Breast cancer cases and female population size data were received from the national cancer registries and the state departments of statistics. The study included 85 132 breast cancers with 150 million person‐years at risk. We estimated annual rayon (district)‐average absorbed doses to the breast from external and internal irradiation of the adult female population over the period of 1986‐2016. We studied an association between rayon‐average cumulative absorbed breast dose with 5‐year lag, that is, excluding the exposure in 5 years prior to breast cancer diagnosis, and breast cancer incidence using negative binomial regression models. Mean (median) cumulative breast dose in 2016 was 12.3 (5.0) milligray (mGy) in Belarus and 5.7 (2.3) mGy in Ukraine, with the maximum dose of 55 mGy and 54 mGy, respectively. Breast cancer incidence rates statistically significantly increased with calendar year and attained age, and were higher in urban than in rural residents. Adjusting for time, age and urbanicity effects, we found no evidence of increasing incidence with rayon‐average 5‐year lagged cumulative breast dose. Owing to ecological study design limitations, a case‐control study covering this area with individually reconstructed absorbed breast doses is needed testing for association between low‐dose protracted radiation exposure and breast cancer risk after Chernobyl. Abstract : What's new? The Chernobyl nuclear accident in 1986 exposed various populations, including nearby residents and cleanup workers, to low‐dose ionizing radiation. Here, using national cancer data and data on radionuclide fallout, the authors investigated associations between breast cancer incidence and ionizing radiation exposure in female populations in the most contaminated regions of Belarus and Ukraine following the Chernobyl accident. Analyses indicate that over the period 1986‐2016, breast cancer incidence did not increase in relation to the average 5‐year lagged cumulative breast dose in urban and rural populations. Possible dose misclassification warrants additional investigation via a case‐control study applying individual breast doses.